MODIFIKASI DESAIN CETAKAN VELG 14 INCH UNTUK SEPEDA MOTOR DENGAN BAHAN PRODUK ALUMINIUM A356 - Sugeng, Margono; Sutajiri, Yusuf (Bina Teknika, 2017)
This studi purpose to modify the design molding of motorcycle 14 inch  used for gravity casting by using CAD/CAM software. Modifications are made with a view to improving the cast product results from previous research. In previous research conducted by the authors obtained the results of wheels products that still occur defects include missrun defects and shrinkage. The scope of this study is review of problems in the previous design, the foundry system design, the modification process, and the parameter determination of the simulation process. Process simulation refers to the temperature parameter of pre-heating mold of 300 and 350 oC with liquid metal pour temperature ranges 800 and 850 oC, and Heat transfer Coefficient = 500 and 700. The parameters of aluminium materials used are aluminum type A356. Analysis of the simulation process is performed to find shrinkage porosity defects that occurred. From the simulation results, the perfect product is a product with pre-heating temperature of 350 oC, 800 oC cast temperature and HTC value = 500, with a shrinkage of porosity 3.16 %.